Efektivitas Diversi dalam Penyelesaian Tindak Pidana di Kepolisian Resor Kota Banyumas - Jeffry Eguh Pangestu; Angkasa Angkasa; Setya Wahyudi (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
This research aims to determine, understand, and analyze elaboratively the effectiveness of implementing diversion and inhibiting factors faced by the police in resolving criminal acts that occur in the jurisdiction of the Banyumas City Police Department. The research method used in this paper is qualitative research with a sociological juridical approach, with analytical descriptive research specifications. The location of this research is at the Banyumas City Police Department. The types and sources of data in this research include primary data and secondary data. Primaries data were obtained through interviews and secondaries data were obtained through literature study which was described narratively and systematically. Based on the research results, it was concluded that the implemention of diversion in resolving criminal acts at the Banyumas City Police Department jurisdiction had been effective in cases that met the material and formal requirements as determined in statutory regulations such as Law Number 11 of 2012 concerning Juvenile Criminal Justice System, Government Regulation Number 65 of 2015 concerning Guidelines for Implementing Diversion and Handling Childen Who Are Not Yet 12 (twelve) Years Old, as well as Police Regulation Number 8 of 2021 concerning Handling Criminal Offenses based on Restorative Justice. Then, regarding the inhibiting factors faced by the police in implementing diversion at the investigation level, they consist of: Legal structure factors, namely the lack of understanding by internal resources, especially police officers at the lowest level (Polsek) regarding the mechanisms and rules for resolving criminal cases through diversion, Legal substance factors, namely the absence of internal police regulations that specifically regulate technical and administrative instructions for investigations (Standard Operational Procedures) relating to the implementation of diversion at the investigative level, (3) Legal culture factors, namely the community at generally, there is still a paradigm that the concept of justice for perpetrators of criminal acts is punishment or criminal imposition which focuses on the aspect of retaliation.